The System Of Training Foreign Personnel At The Academy Of The Ministry Of Internal Affairs Of The Republic Of Uzbekistan (Eurasian Journal of History, Geography and Economics, 2026)
This article analyzes the role and importance of training foreign personnel within the educational system of internal affairs bodies, its main directions, and the specific characteristics of this process, using the Academy of the Ministry of Internal Affairs of the Republic of Uzbekistan as a case study. The article examines the legal and regulatory framework for international cooperation, current educational programs, their effectiveness, and existing shortcomings. Furthermore, it provides practical recommendations for the further improvement of this field